The use of guided endodontics for fiberglass pin removal: clinical case report (Research, Society and Development, 2022)
The use of endodontic guide is a minimally invasive technique, indicated for the treatment of calcified canals, resuming the original trajectory of the canal, in cases of deviation and/or perforation, removal of fiberglass post and even guided parendodontic surgery. The use of endodontic guide currently presents good predictability, safety and speed in the treatment of complex cases, to which it will be attributed. The technique is so precise that it does not depend on the operator and can be performed by even less skilled professionals. The objective of this work was to report a clinical case of removal of a fiberglass post in element 11, due to a failure in the prosthetic treatment, using an endodontic guide (endoguide).